Deleterious Role of Th9 Cells in Pulmonary Fibrosis - Kui Miao Deng (MDPI AG, 2021)
Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal lung disease of unknown etiology. Immune disorders play an important role in IPF pathogenesis. Here, we show that Th9 cells differentiate and activate in the lung tissue of patients with IPF and bleomycin (BLM)-induced lung fibrosis mice. Moreover, we found that Th9 cells promote pulmonary fibrosis in two ways. On the one hand, Th9 cells promote fibroblast differentiation, activation, and collagen secretion by secreting IL-9. On the other hand, they promote differentiation of Th0 cells into Th2 cells by secreting IL-4. Th9 cells and Th2 cells can promote each other, accelerating the Th1/Th2 imbalance and eventually forming a positive feedback of pulmonary fibrosis. In addition, we found that neutralizing IL-9 in both preventive and therapeutic settings ameliorates bleomycin-induced pulmonary fibrosis. Furthermore, we identified several critical signaling pathways involved in the effect of neutralizing IL-9 on pulmonary fibrosis by proteomics study. From an immunological perspective, we elucidated the novel role and underlying mechanism of Th9 cells in pulmonary fibrosis. Our study suggested that Th9-based immunotherapy may be employed as a treatment strategy for IPF.